2016
DOI: 10.1155/2016/5296048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subfoveal Choroidal Thickness in Internal Carotid Artery Stenosis

Abstract: Purpose. To evaluate the relationship between internal carotid artery (ICA) stenosis and subfoveal choroidal thickness (SFCT) in the elderly population. Methods. A total of 42 eyes of 21 patients with more than 70% ICA stenosis (Group 1) on one side and less than 70% stenosis (Group 2) on the other side were recruited for this study. ICA stenosis was diagnosed using both the B-mode and Doppler ultrasound. The two groups were compared in terms of the percentage of stenosis, SFCT measurements, intraocular pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Similarly, Sayin et al compared the eyes of severe ICAS patients with those of healthy volunteers and found a significantly thinner central choroid in the former group [29]. On the other hand, Akçay et al found that the choroid was thicker in patients with unilateral significant ICA stenosis in a presumable mechanism of compensatory enlargement of the choriocapillaris vasculature to prevent retinal and choroidal ischaemia as a result of the diminished blood flow due to ICA stenosis [17]. Significantly, the young age of our study participants may provide some explanation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Sayin et al compared the eyes of severe ICAS patients with those of healthy volunteers and found a significantly thinner central choroid in the former group [29]. On the other hand, Akçay et al found that the choroid was thicker in patients with unilateral significant ICA stenosis in a presumable mechanism of compensatory enlargement of the choriocapillaris vasculature to prevent retinal and choroidal ischaemia as a result of the diminished blood flow due to ICA stenosis [17]. Significantly, the young age of our study participants may provide some explanation.…”
Section: Discussionmentioning
confidence: 99%
“…e blood supply to the choroid arises from the ophthalmic branch of the internal carotid artery (ICA) via the short ciliary arteries [17,29]. Stenosis of the ICA results in the reduction of arterial pressure distal to the stenosis, including brain and ocular circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Studies have also found that CT reduction is associated with increased arterial stiffness. 28,30,31 Because the choroidal blood vessels nourish the outer retinal layer and RPE, it is possible that retinopathy is secondary to choroidal damage. Dysfunction of the autonomic nervous system can also cause CT changes, and overactivation of the sympathetic nervous system is a feature of DN.…”
Section: Discussionmentioning
confidence: 99%
“…We have read the article entitled “Evaluation of Subfoveal Choroidal Thickness in Internal Carotid Artery Stenosis” by Akçay et al with great interest [ 1 ]. The authors researched the relationship between internal carotid artery (ICA) stenosis and subfoveal choroidal thickness (CT) in the elderly population.…”
mentioning
confidence: 99%